Tailoring the formation of twins in Al by introducing epitaxial layer interfaces. (February 2021) - Xue, S.C.; Zhang, Y.F.; Li, Qiang; Ding, Jie; Wang, H.; Zhang, X.
Abstract: Twin boundaries have enabled unique mechanical and physical properties in metallic materials. However, growth twins are rarely observed in Al due to its high stacking fault energy. In this study, we report on the synthesis of high-density growth twins in sputtered Al/Mg multilayer films. The formation mechanisms of incoherent and coherent twin boundaries are discussed. Besides, the incoherent twin boundary related structure, 9R phase, was also identified. This study highlights an effective method to elevate the twin /9R phase density in metals with high stacking fault energy. Graphical Abstract: Image, graphical abstract